2021
DOI: 10.3390/urbansci5010021
|View full text |Cite
|
Sign up to set email alerts
|

Innovations and Economic Output Scale with Social Interactions in the Workforce

Abstract: The COVID-19 pandemic of 2020 fundamentally changed the way we interact with and engage in commerce. Social distancing and stay-at-home orders leave businesses and cities wondering how future economic activity moves forward. The reduction in face-to-face interactions creates an impetus to understand how social interactivity influences economic efficiency and rates of innovation. Here, we create a measure of the degree to which a workforce engages in social interactions, analyzing its relationships to economic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Social IWAs are defined as those likely to require face-to-face interaction between employees. Painter et al [ 27 ] recently demonstrated that the spatial density of social ONET elements is positively correlated with patenting output of cities and that the number of social IWAs per worker in an industry is superlinearly related to the industry’s per worker GDP. Thus, socialness is positively correlated with both innovation and productivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Social IWAs are defined as those likely to require face-to-face interaction between employees. Painter et al [ 27 ] recently demonstrated that the spatial density of social ONET elements is positively correlated with patenting output of cities and that the number of social IWAs per worker in an industry is superlinearly related to the industry’s per worker GDP. Thus, socialness is positively correlated with both innovation and productivity.…”
Section: Discussionmentioning
confidence: 99%
“…As with elements, IWAs must be mapped to BLS occupations codes. Since there is no value to collapse by averaging, we adopt the method used in [ 27 ] to assign a present/absent indicator for each BLS occupation. If an activity is present in any one of the ONET occupations that map to a single BLS occupation, it is designated as present in the BLS occupation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation